2013
DOI: 10.14573/altex.2013.3.331
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism and bioavailability tests for endocrine active substances: What is needed next for regulatory purposes?

Abstract: SummaryLegislation and prospective legislative proposals internationally (may)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 101 publications
(100 reference statements)
0
36
0
Order By: Relevance
“…Incorporation of phase I and II enzymes into test cell lines through genetic engineering is also currently technically challenging due to decreased cell viability when too many P450s are expressed in the same cells (Coecke et al, 2006). In a follow-up paper, Jacobs et al (2013) described the general lack of progress in developing and standardizing methods to incorporate metabolic and toxicokinetic aspects into in vitro assays. The lack of metabolic competency in in vitro assays remains one of the most highly cited limitations in predictive toxicity methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of phase I and II enzymes into test cell lines through genetic engineering is also currently technically challenging due to decreased cell viability when too many P450s are expressed in the same cells (Coecke et al, 2006). In a follow-up paper, Jacobs et al (2013) described the general lack of progress in developing and standardizing methods to incorporate metabolic and toxicokinetic aspects into in vitro assays. The lack of metabolic competency in in vitro assays remains one of the most highly cited limitations in predictive toxicity methodology.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to consider the absorption, distribution and the metabolism of the substance in the human organism, the metabolism and interaction among organs (Yoon et al, 2012;Jacobs et al, 2013). This fundamental aspect is often underestimated.…”
Section: Comparison Of the European And American Approachesmentioning
confidence: 99%
“…Several EDCs are known to undergo fast metabolic transformation and some pathways are induced by metabolites rather than by the parent compounds. However, in vitro assays that incorporate metabolizing systems still need to be validated (Jacobs et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of metabolite simulators differs depending on the software and target chemical but can range from 50% to even 93% (Shin et al, 2011;T'Jollyn et al, 2011). Jacobs et al (2013) suggested that in silico systems that predict metabolites can provide input for quantitative structure-activity relationship (QSAR) models to assess the effects of untested metabolites.…”
Section: Introductionmentioning
confidence: 99%